PERUBAHAN KEBIJAKAN DI SEKTOR MIGAS PASCA REZIM ORDE BARU - Syamsul Ma’arif (Program Studi Administrasi Negara Universitas Serang Raya, 2013)
Monetary crisis that later developed wide become economic crisis at the end of 1997 had cripled the government capacity in providing material resources for the people. Politically, the crisis had made people’s support decline and created low trust over the government. In order to protect the existence, the government demanded support of the international finance institution especially IMF. Consequently, weak bargaining position of the government made the government could’nt avoid political intervention of IMF and other international finance institution which were so dominant in forcing the government to change economy policy radically. One of policy change was done through liberalization of petroleum sector as a sector which had been regulated strickly by the government for a long time. Lesson learn that could be taken were: firstly, situation of crisis created pressure to change policy radically; secondly, need of capital injection in large number from abroad had made policy change be domined by international capitalist.